Early care in children with neurodevelopmental disorders - Ponce-Meza, Jacqueline (2017)
The article analyzes the importance of early care in child development, guiding a neuropsychological perspective of development. The early care model seeks to refer to the set of interventions aimed at children and their work in conjunction with a multidisciplinary team. It presents recommendations for the implementation of programs that allow early intervention in the early years, so that the process of care for the affected children can be optimized by the different early developmental and learning alterations.